2003
DOI: 10.1128/iai.71.9.5344-5354.2003
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Is Essential for Virulence in Candida albicans

Abstract: Calcineurin is a conserved Ca2؉ -calmodulin-activated, serine/threonine-specific protein phosphatase that regulates a variety of physiological processes, e.g., cell cycle progression, polarized growth, and adaptation to salt and alkaline pH stresses. In the pathogenic yeast Cryptococcus neoformans, calcineurin is also essential for growth at 37°C and virulence. To investigate whether calcineurin plays a role in the virulence of Candida albicans, the major fungal pathogen of humans, we constructed C. albicans m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 55 publications
3
102
1
2
Order By: Relevance
“…62,71,72 These in vitro results are supported by gene deletion studies showing that calcineurin-defective C. albicans mutants were more sensitive to stress conditions than isogenic wild-type controls, were markedly hypersensitive to azoles, and had attenuated virulence in mice with systemic candidiasis. [73][74][75] Although that hypovirulence is attributed to sensitivity of C. albicans to killing by serum mediated by Ca 2+ , no reported data have indicated that pharmacological inhibition of calcineurin also protects against calcium stress. Interestingly, loss of function crz1 C. albicans mutants, defective in crz1 which encoded a downstream transcription effector of the calcineurin, Crz1, were not sensitive to serum and exhibited no decrease in virulence.…”
Section: Inhibitors Of Calcineurin and Tormentioning
confidence: 99%
“…62,71,72 These in vitro results are supported by gene deletion studies showing that calcineurin-defective C. albicans mutants were more sensitive to stress conditions than isogenic wild-type controls, were markedly hypersensitive to azoles, and had attenuated virulence in mice with systemic candidiasis. [73][74][75] Although that hypovirulence is attributed to sensitivity of C. albicans to killing by serum mediated by Ca 2+ , no reported data have indicated that pharmacological inhibition of calcineurin also protects against calcium stress. Interestingly, loss of function crz1 C. albicans mutants, defective in crz1 which encoded a downstream transcription effector of the calcineurin, Crz1, were not sensitive to serum and exhibited no decrease in virulence.…”
Section: Inhibitors Of Calcineurin and Tormentioning
confidence: 99%
“…15 The signaling by calcium is very important for fungal virulence and drug resistance. 1,2 Calcineurin has been demonstrated to be required for virulence in human fungal pathogens, such as Cryptococcus spp, Candida spp, Paracoccidioides brasiliensis, and Aspergillus fumigatus; [16][17][18][19][20][21][22][23] and fungal plant pathogens, such as Sclerotinia scleotiorum, Botrytis cinerea, Magnaporthe oryza, and Ustilago spp. [24][25][26][27][28] In all these fungal pathogens, calcineurin is important for growth, morphology, state transitions, cation homeostasis, stress responses, and cell membrane and cell wall integrity pathways.…”
Section: Introductionmentioning
confidence: 99%
“…All these components showed a high degree of sequence identity (40-90%) among the fungal species studied. In the human pathogens C. albicans, C. neoformans and A. fumigatus, calcineurin was required for survival in serum and for virulence (Bader et al, 2003;Blankenship et al, 2003;Da Silva Ferreira et al, 2007;Fox et al, 2001;Odom et al, 1997;Steinbach et al, 2006Steinbach et al, , 2007. In the plant pathogen Sclerotinia sclerotiorum, the calcineurin orthologue controls sclerotial development and infection (Harel et al, 2006).…”
Section: The Calcium/calcineurin Signalling Pathwaymentioning
confidence: 99%